(untitled) (Research, Society and Development, 2021)
This study evaluated the anticholinesterase, antimicrobial and fungicidal activities of the fixed oil from araticum seeds (Annona coriacea Mart., Annonaceae family), obtained with ethanol as an extracting solvent. The fixed oil was tested in vitro against the enzyme acetylcholine, gram-positive (Staphylococcus aureus and S. epidermides) and gram-negative (Escherichia coli and Pseudomonas aeruginosa) bacterial strains, and fungi (Candida albicans, C. krusei, Neoscytalidium dimidiatum and Fusarium sacchari). Fixed oil proved to be an inhibitor of the acetylcholinesterase enzyme, with inhibition varying from 37 to 84%. It was inactive against gram-positive, gram-negative bacteria and fungi, with MIC ≥1024, through the antimicrobial assay. It allowed control of mycelial growth of N. dimidiatum in the five doses tested (0.1, 0.5, 1.0, 2.0 and 3.0 µL mL-1). There was no significant control against F. sacchari, doses 1, 2 and 3 (0.1, 0.5 and 1.0 µL mL-1) showed low percentages of inhibition, while doses 4 and 5 showed control, however, it did not differ from mycelial growth in the control treatment with culture medium. It can be concluded that the fixed oil from araticum seeds is a strong candidate for the development of phytopharmaceuticals based on A. coriacea against pathogenic fungi.